Acoustic signature of flow instabilities in radial compressors. (10th November 2018) - Sundström, Elias; Semlitsch, Bernhard; Mihăescu, Mihai
Abstract: Rotating stall and surge are flow instabilities contributing to the acoustic noise generated in centrifugal compressors at low mass flow rates. Their acoustic generation mechanisms are exposed employing compressible Large Eddy Simulations (LES). The LES data are used for calculating the dominant acoustic sources emerging at low mass flow rates. They give the inhomogeneous character of the Ffowcs Williams and Hawkings (FW-H) wave equation. The blade loading term associated with the unsteady pressure loads developed on solid surfaces (dipole in character) is found to be the major contributor to the aerodynamically generated noise at low mass flow rates. The acoustic source due to the velocity variations and compressibility effects (quadrupole in character) as well as the acoustic source caused by the displacement of the fluid due to the accelerations of the solid surfaces (monopole in character) were found to be not as dominant. We show that the acoustic source associated with surge is generated by the pressure oscillation, which is governed by the tip leakage flow. The vortical structures of rotating stall are interacting with the impeller. These manipulate the flow incidence angles and cause thereby unsteady blade loading towards the discharge. A low-pressure sink between 4 and 6 o'clock causes a halving of the perturbation frequencies at low mass flow rates operating conditions. From two point space-time cross correlation analysis based on circumferential velocity in the diffuser it was found that the rotating stall cell propagation speed increases locally in the low pressure zone under the volute tongue. It was also found that rotating stall can coexist with surge operating condition, but the feature is then seen to operate over a broader frequency interval.